STRATEGI PEMERINTAH KOTA SURABAYA DALAM PENGELOLAAN SENTRA IKAN BULAK DI WILAYAH PESISIR - Evita Dwi Setiani Putri; Agus Widiyarta (Universitas Djuanda Bogor, 2023)
The development of the Bulak Fish Center is an effort by the Government Municipal to create a platform for street vendors to increase economic income. However, there is a problem with the Bulak Fish Center, which has been functioning as a centre for marine products and crafts, which is still quiet, so traders return to selling on the side of the road. Therefore, a city government strategy is needed to manage Bulak Fish Centers. This study used the Wheelen & Hunger Strategy Theory of environmental scanning, strategy formulation, strategy implementation, evaluation and control. The purpose of this study was to determine the Government Municipal Strategy for Managing Bulak fish Centers in the Coastal Area of ​​Surabaya City. This study used a descriptive qualitative method. Information was obtained through interviews, observation, documentation and literature study. The researcher selects informants based on purposive sampling, namely selecting samples or informants who are considered to be related to the matter to be studied based on the subject matter supported by relevant data and providing comprehensive data on the research problem. As for the informants, namely the fisheries and maritime affairs of the Food Security and Agriculture Service. The data analysis technique used interactive with the steps of data collection, data condensation, data presentation and drawing conclusions. Based on the results of field analysis, the government muncipal strategy has been implemented well, but the researchers suggest a strategy to be more stringent in regulations by assisting traders and outreach. Recommendations for future researchers who will carry out similar research are to increase the time needed so that the results obtained are maximum and more absolute.